High Compliance with the 11+ Injury Prevention Program Results in Better Win-Loss Records - Holly Silvers-Granelli; Mario Bizzini; Bert Mandelbaum; Amelia Arundale; Ryan Pohlig; Lynn Snyder-Mackler (North American Sports Medicine Institute, 2023)
# Background The 11+ injury prevention program (IPP) has been shown to decrease injury rates. However, few studies have investigated compliance and its overall relationship to team performance. # Hypothesis/Purpose To examine if level of compliance while implementing the 11+ would impact team performance outcomes (wins, losses and ties). The authors hypothesized that higher team compliance to the IPP would be consistent with improved overall team performance (more wins and fewer losses). # Study Design Prospective, cluster randomized controlled trial # Methods This study was conducted in NCAA men's soccer teams for one season and examined the efficacy of the 11+ IPP. The outcome variables examined were levels of compliance and team performance record: wins, losses, and ties. Twenty-seven teams (n=675 players) served as the intervention group (IG) and used the 11+ program while 34 teams (n=850 players) served as the control group (CG). Compliance and team performance were recorded. There were three compliance categories that were defined prospectively, low (LC, \< 1 dose/week), moderate (MC, \>1 and \<2 doses/week), and high (HC, \>2 doses/week). Descriptive and inferential tests were used to compare the CG, the IG, and compliance to team performance. Three independent t-tests were used to analyze outcome to group (IG vs. CG). A one way-MANOVA test was used to analyze compliance to win/loss/tie record, followed up by one-way ANOVA tests to analyze how compliance impacted wins, losses and ties, independently. Partial η2 measures were calculated to determine the effect size of level of compliance on outcome. A Tukey post-hoc analysis was used to analyze specific differences between levels of compliance and specific outcome measures. # Results There were significantly more wins (IG: 10.67±2.63 versus CG: 8.15±3.83, CI, 7.95 -- 9.69, p = 0.005) and fewer losses (IG: 5.56±1.97 versus CG: 8.12±3.59, CI, 5.66 to 7.43, p = 0.002) recorded for the teams using the 11+ program. There was a statistically significant difference between levels of compliance (high, moderate or low) on the dependent variables (wins, losses, and ties), F(3, 22) = 3.780, p =0.004; Wilks' Λ = .435; partial η2 = .340. # Conclusion The 11+ has the capacity to improve overall team performance in male collegiate soccer teams. The higher the compliance, the more favorable the team performance. This research may be a vital addition when attempting to persuade coaching staffs to adopt an IPP into their training regimen. # Level of Evidence Level I